2009
DOI: 10.1371/journal.pgen.1000521
|View full text |Cite
|
Sign up to set email alerts
|

A Tether for Woronin Body Inheritance Is Associated with Evolutionary Variation in Organelle Positioning

Abstract: Eukaryotic organelles evolve to support the lifestyle of evolutionarily related organisms. In the fungi, filamentous Ascomycetes possess dense-core organelles called Woronin bodies (WBs). These organelles originate from peroxisomes and perform an adaptive function to seal septal pores in response to cellular wounding. Here, we identify Leashin, an organellar tether required for WB inheritance, and associate it with evolutionary variation in the subcellular pattern of WB distribution. In Neurospora, the leashin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
76
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 46 publications
5
76
0
Order By: Relevance
“…After WB biogenesis in the peroxisome membrane, the newly formed WB should be moved near a septal pore if it is to contribute to septal-pore sealing. In this relocation of the organelle, the Leashin (Lah) gene product is responsible for WB tethering (22). It is also well known that some plant viruses use peroxisomes for their viral replication (43).…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…After WB biogenesis in the peroxisome membrane, the newly formed WB should be moved near a septal pore if it is to contribute to septal-pore sealing. In this relocation of the organelle, the Leashin (Lah) gene product is responsible for WB tethering (22). It is also well known that some plant viruses use peroxisomes for their viral replication (43).…”
Section: Figmentioning
confidence: 99%
“…Especially in the case of Tomato bushy stunt virus (TBSV), viral RNA replication occurs on the surface of the cytosolic membrane of peroxisomes in plants and in yeast (44). Based on the previous reports concerning WB biogenesis (21,22,42) and RNA viral replication on peroxisomes and on the current results concerning the presence of gene homologs related to WB biogenesis in F. graminearum (WSC for locus FGSG_01049 and Lah for locus FGSG_04119), it is tempting to speculate that FgV1 or other potential mycoviruses might use this tethering process to facilitate the accumulation and intracellular movement of viral RNAs.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Although filamentous fungi are classified as multicellular organisms, septa do not completely separate adjacent hyphal cells due to the presence of a septal pore, which allows the passage of cytoplasm and organelles between adjacent cells (1)(2)(3). Cytoplasmic continuity through the septal pore is associated with the catastrophic risk of cytoplasmic loss in the event of hyphal wounding.…”
mentioning
confidence: 99%
“…If size does not matter, and the developmental complexity and tissue differentiation seen in these microscopic fungi reflect that seen in mushrooms and truffles, comparison of genetically tractable species with C. cinerea and relatives should also pay dividends. A pair of membranous organelles worth investigating might be the Woronin body of Ascomycota and the septal pore complex of Basidiomycota, which function to seal damaged hyphae and might have been instrumental in allowing fungi to make complex, multicellular structures (19). Making the comparisons suggested herein, most of which can be attempted with existing genome assemblies, might not only unravel the basis of fungal complexity, but point the way for studies of plants and animals, as more of the much larger genomes found in those kingdoms become available.…”
mentioning
confidence: 99%